Dosimetry of short-ranged radionuclides - Lassmann, M. (Nuklearmedizin - NuclearMedicine, 2010)
More and more targeted radiotherapies (TRT) are carried out with pure beta-emitters such as 90Y. Normally fixed activities are administered without considering the individual biokinetics increasing the risk of under- or overdosing. In addition, it would be helpful to obtain additional data on dose-response relationships for further optimization of TRTs. Therefore, post-therapeutic dosimetry using quantitative imaging becomes more important. For an optimization of TRTs additional aspects such as the changing dose rate and radio biological considerations need to be taken into account.This paper provides an overview on bremsstrahlung imaging modalities after therapies with pure beta-emitters. In addition, new dosimetric methods are described which consider dose rate and fractionation of treatment.
Keywords: Dosimetry; Bremsstrahlung; SPECT; PET